2019
DOI: 10.1007/s10750-019-04011-4
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter resources fuelling food webs in a human-modified lowland river: importance of habitat and season

Abstract: The role of hydromorphological degradation and temporal variation for food webs in humanmodified rivers is still not fully evaluated. We tested the hypothesis that man-made engineering structures alter macroinvertebrate resource use in the Elbe River (Germany) in relation to seasonal variation. Stable isotopes (d 13 C, d 15 N) and mixing models revealed that dietary contributions of benthic organic matter (BOM) and phytoplankton were driven by engineering structure. Contributions of biofilm were driven by seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Standing stocks of terrestrial POM (t-POM) were not quantified during the study, and we instead took values from the literature for similarsized rivers (Benfield, 1997) (Table 1). Detailed information on sampling processing and isotope analysis, as well as mixing model analysis for macroinvertebrate primary consumers, are provided elsewhere (Brauns et al, 2019). For this study, we quantified the proportion of assimilated prey for omnivorous or macroinvertebrate predators initially at the mesohabitat-scale at each engineering structure.…”
Section: Construction Of Food Websmentioning
confidence: 99%
See 2 more Smart Citations
“…Standing stocks of terrestrial POM (t-POM) were not quantified during the study, and we instead took values from the literature for similarsized rivers (Benfield, 1997) (Table 1). Detailed information on sampling processing and isotope analysis, as well as mixing model analysis for macroinvertebrate primary consumers, are provided elsewhere (Brauns et al, 2019). For this study, we quantified the proportion of assimilated prey for omnivorous or macroinvertebrate predators initially at the mesohabitat-scale at each engineering structure.…”
Section: Construction Of Food Websmentioning
confidence: 99%
“…Our previous work showed that macroinvertebrate secondary production is lower at hydromorphologically altered shores (Brabender, Weitere, Anlanger, & Brauns, 2016) and that the trophic basis of macroinvertebrate primary consumers varies with the degree of hydromorphological alteration (Brauns, Brabender, Gehre, Rinke, & Weitere, 2019).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…sites or subspecies. We tested which of these factors was more important using the 'overlapping' package [40] in R as outlined by Brauns et al [41]. We used the 95% credibility intervals of dietary proportions across the studied locations and two subspecies, and calculated the percentage overlap of these intervals between all combinations of sites as well as subspecies.…”
Section: Stable Isotope Analysismentioning
confidence: 99%